Fabrication of Aligned-Carbon-Nanotube-Composite Paper with High and Anisotropic Conductivity. (15th August 2012) - Fujitsuka, Yuki; Oya, Takahide
Abstract : A functional carbon-nanotube (CNT)-composite paper is described in which the CNTs are aligned. This "aligned-CNT composite paper" is a flexible composite material that has CNT functionality (e.g., electrical conductivity) despite being a paper. An advanced fabrication method was developed to overcome the problem of previous CNT-composite papers, that is, reduced conductivity due to random CNT alignment. Aligning the CNTs by using an alternating current (AC) field was hypothesized to increase the electrical conductivity and give the paper an anisotropic characteristic. Experimental results showed that a nonionic surfactant was not suitable as a CNT dispersant for fabricating aligned-CNT composite paper and that catechin with its six-membered rings and hydrophilic groups was suitable. Observation by scanning electron microscopy of samples prepared using catechin showed that the CNTs were aligned in the direction of the AC field on the paper fibers. Measurement of the electric conductivity showed that the surface resistance was different between the direction of the aligned CNTs (high conductivity) and that of verticality (low). The conductivity of the aligned-CNT-composite paper samples was higher than that of nonaligned samples. This unique and functional paper, which has high and anisotropic conductivity, is applicable to a conductive material to control the direction of current.